Highly Nanoporous Nickel Cobaltite Hexagonal Nanostructure‐Graphene Composites for the Next Generation Energy Storage/Conversion Devices. Issue 16 (10th July 2017) - Annamalai, Kundrakudi Ponsubramanian; Liu, Lile; Tao, Yousheng
Abstract : The design and assembly of innovative heterostructures comprising of multifunctional properties are technically important for the applications in efficient energy devices. Here, a novel method is reported to construct hierarchical nanostructures as functional materials for the fabrication of high‐performance energy devices. Optimized conditions and extensive spectroscopic studies are performed to understand the morphology evolution. Tunable structure, richer redox active sites, enhanced mass storage, and fast electron transfer cumulatively ensure the tremendous energy storage competence. Resultant active nanomaterials of nickel cobaltite‐graphene coupled with nanoporous graphene‐single wall carbon nanohorns composites exhibit extraordinary energy density of 70.5 Wh kg −1 . Meanwhile, this nickel cobaltite‐graphene is also recognized as a prominent water oxidation catalyst, which requires low overpotential of 220 mV to afford 20 mA cm −2 current density. High performance with availability, low cost, and subtle structural distinction acknowledge that the present approach is a promising direction in pursuit of replacing precious metals in energy storage and conversion technologies. Abstract : Design and synthesis of highly nanoporous metal oxide composites with simple and cost effective method are promising for efficient energy devices, which not only allow bulk scale production but also reduce the device fabrication cost to a larger extent.